Partners’ abnormal audit hours on the subsidiaries of conglomerate group and audit qualities* - Kim, Sang Il; Kim, Kyung Tae (Korean Accounting Review, 2020)
This study tests the possibility of external audit partner’s audit quality impairment according to the expected audit fees of other affiliates of the specific audit clients. For empirical analysis, we adopt four types of discretionary accruals to measure audit qualities for 2,007 firm-year observations listed on KSE and KOSDAQ market during 2015 to 2018. The empirical results are summarized as follows. First, the higher expected audit fees of other affiliates in the same conglomerate group lead to the abnormal audit hours of the audit partner for the audit client. Second, the higher the expected audit fee of other affiliates in the same conglomerate group, the partner's abnormal audit hours lead to lower audit quality. The finding suggests that audit partners care for other affiliates of the conglomerate group and lower audit quality to attract more clients from the conglomerate group. In addition, the regulation related to the prohibition of the simultaneous provision of audit and non-audit services among affiliate firms in a conglomerate group, enforced in 2017, weakens the documented association.
Keywords: Audit quality; Chaebol; Conglomerate group; Partners’ audit hour